Holding our ground - Henderson,Anne.; Wilson, David; National Film Board of Canada ([Ottawa] National Film Board of Canada, 1988)
A story of an organized group of Filipino women who demands government support for land reform, shelters for street children, and logistics for a money lending system.
VHS
Keywords: Women in politics -- Philippines; Abandoned children -- Philippines; Land reform -- Philippines; Women's rights -- Philippines; Philippines -- Social conditions